Effects of Share 35 Policy on Liver Transplantation Outcomes for Patients With Nonalcoholic Steatohepatitis. (September 2019) - Zhang, Yefei; Boktour, Maha R.
Background: To examine the temporal variation and outcomes of liver transplantation between pre- and post-Share 35 eras for patients with nonalcoholic steatohepatitis. Methods: A retrospective analysis was performed among 4380 patients with end-stage liver disease from the United Network for Organ Sharing database from 2009 to 2017 due to primary diagnosis of nonalcoholic steatohepatitis or cryptogenic cirrhosis with body mass index greater than 30. Cox regressions were used to model the effect of Share 35 policy on patient and graft survival comparing the first 3 years of Share 35 policy to an equivalent time period before. Results: The number of nonalcoholic steatohepatitis-related transplants increased from 232 (14.1%) in 2009 to 266 (20.5%) in 2017. In post-Share 35 era, average waitlist time and cold ischemic time decreased, while Model for End-Stage Liver Disease (MELD) scores increased with higher proportion of recipients having MELD ≥35. No significant difference in average length of hospitalization or survival was found after Share 35. Conclusions: The Share 35 policy benefits patients with nonalcoholic steatohepatitis from reduced liver transplantation waiting time. It is also associated with comparable outcomes in 2 eras without increasing cold ischemic time or posttransplant length of hospitalization.